Association between Cadre Knowledge, Feeding Behaviours and Daily Intake with Changes in Nutritional Status of Undernourished Children in Kawangu Health Centre, East Sumba - Maria Kareri Hara; Kadek Tresna Adhi; Alex Pangkahila (Universitas Udayana, 2014)
Background and purpose: In 2012, in Eastern Sumba 21% of children under 5 were malnourished; at the Kawangu Health Centre (KHC) it was reported that 3.4% of children were underweight. This study aims to investigate relationships between cadre knowledge, motivation and behavior of child carers with the nutritional status changes of children from KHC. Methods: A cross-sectional study with 80 samples was conducted. Variables were cadre knowledge, motivation, feeding behaviors and change in nutritional status. Data on cadre knowledge and motivation was collected through a self-administered questionnaire and through interviews conducted with child carers. Anthropometric measurements were taken to assess changes in nutritional status of children. Analysis used univariate and bivariate chi-square test. Results: Results indicated respondents were aged 26-35 (41.2%), had elementary school education (56.2%), were farmers (91.2%), had experience as cadres for 2 years (53.8%), were trained (72.5%) and had been involved with the program less than <45 days (91.2%). About 55.0% of respondents indicated a high level of knowledge and were highly motivated (86.2%). Carers indicated a fair behaviour change (51.2%), although there was an increase in improvement in nutritional status (63.8%). There was relationship between cadre knowledge and changes in feeding behaviours (p=0.016), but not with cadre motivation (p=0.500). There was an association between feeding behavior (p=0.032) with changes in nutritional status. Conclusion: The good levels of cadre knowledge and high quality feeding practices impacted positively upon improvements in child nutritional status.